The age of foundation models - Lipkova, Jana; Kather, Jakob Nikolas (Nature reviews. Clinical oncology, 2024)
The development of clinically relevant artificial intelligence (AI) models has traditionally required access to extensive labelled datasets, which inevitably centre AI advances around large centres and private corporations. Data availability has also dictated the development of AI applications: most studies focus on common cancer types, and leave rare diseases behind. However, this paradigm is changing with the advent of foundation models, which enable the training of more powerful and robust AI systems using much smaller datasets.
Gesehen am 28.02.2025